2018
DOI: 10.1186/s12876-018-0891-y
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of distant metastasis on exploration in patients with potentially resectable pancreatic cancer

Abstract: BackgroundPatients with potentially resectable pancreatic ductal adenocarcinoma (PDAC) are frequently found to be unresectable on exploration due to small distant metastasis. This study was to investigate predictors of small distant metastasis in patients with potentially resectable PDAC.MethodsPatients who underwent surgical exploration for potentially resectable PDAC from 2013 to 2014 were reviewed retrospectively and divided into two groups according to whether distant metastases were encountered on explora… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
34
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(39 citation statements)
references
References 43 publications
5
34
0
Order By: Relevance
“…Regarding the tumor size and location, our results were consistent with previous studies (2,3,22,23). The larger the tumor, the more likely it is to have distant metastasis.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Regarding the tumor size and location, our results were consistent with previous studies (2,3,22,23). The larger the tumor, the more likely it is to have distant metastasis.…”
Section: Discussionsupporting
confidence: 92%
“…(I-J) Follow up PET/MR 112 days after operation showed the operated region with hyper-intensity in T2 weighted image with fat saturation (J) and without abnormal FDG uptake on PET image (I). (2,22). In a cohort of 1,423 patients with PDAC who underwent pancreatectomies, the occurrence of occult metastatic disease in PDAC accounted for 8% of cases, and multivariable analysis defined four independent predictors for occult metastatic disease (3).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Tumor size was an independent risk factor for the occurrence of distant metastasis in pancreatic cancer, and the size of less than 5 cm was higher rate of distant metastasis compared with other size [4]. Previous study also has reported that the younger age, sex, larger size, low ALT and high CA19-9 are thought to be associated with distant metastasis [5]. Unluckily, so far very few studies have explored the risk factors of distant metastasis for LN + pancreatic tumors.…”
Section: Introductionmentioning
confidence: 85%
“…Most PDAC patients are diagnosed with metastatic disease, and majority of patients will develop metastatic disease even after the localized lesions are resected [27,28]. Therefore, the development of more effective strategies to combat PDAC metastasis is of paramount importance.…”
Section: Discussionmentioning
confidence: 99%